Elaboration of the Piezometric Map of the Superficial Aquifers of the Town of Isiro (Haut- Uélé, DR Congo) - Faidance Mashauri; Mokili Mbuluyo (Budapest International Research and Critics University, 2022)
This study developed in the town of Isiro in the province of Haut-Uélé, in the north-east of the Democratic Republic of the Congo, made it possible to produce a piezometric map of the superficial aquifers of this town using the triangle interpolation method. The quality of the groundwater studied was assessed by analysing a number of physico-chemical (temperature and pH) and bacteriological (total coliforms, faecal coliforms, faecal streptococcus and Escherichia coli) parameters. Two major superficial hydrogeological units have been defined, one unit consisting of lateritic formations and the other of ancient and modern Quaternary alluvium. The groundwater flow is mainly local, with water flowing over short distances from topographically high points. The hydraulic gradient varies between 0.02 (or 2%) and 0.06 (or 6%) with an average of 0.038 (or 3.8%). The depth map of the piezometric surface indicates that the water table is deeper on the plateaus (over 7m) than in the valleys. The flow rates of the springs vary according to the amount of rainfall. Temperatures ranged from 23.7 to 30.9°C. The pH values show that the analysed waters are strongly to slightly acidic (pH between 3.5 and 6.6). The groundwater studied shows a high level of bacteriological pollution.